Strategi Pengembangan Usaha Budidaya Rumput Laut di Desa Warialau Kecamatan Aru Utara Kabupaten Kepulauan Aru - Ngosiem, Justhine Carmila; Tetelepta, Johannes M. S.; Tuhumury, Semuel F. (Indonesian Journal of Sustainable Aquaculture, 2024)
The aim of this research is to determine the strategy for developing seaweed cultivation businesses in Warialau village, North Aru sub-district, Aru Islands district. To evaluate the sustainability status of seaweed, it is necessary to review the ecological, economic, technological, social and institutional dimensions. This research uses two types of data collection methods, namely primary and secondary data. The results of the ecological dimension analysis show that the physical and chemical water data is in the normal range, the economic dimension shows that the average income of the community is not proportional to the expenditure from seaweed cultivation activities, namely IDR 1,825,000 from capital of IDR 2,800,000. The technology used is relatively simple, both for the seeds used and post-harvest handling. Measurement of the social dimension shows that the majority of the community is at senior high school level 57.1%, followed by junior high school 22.9%, elementary school 14.3% and undergraduate 5.7%. The cultivation system is carried out individually because there is no official institution regarding seaweed development in the future. SWOT and AHP Rapfish were used to test the sustainability of seaweed cultivation businesses in Warialau Village. The Rapfish test results show a 60.5% chance of sustaining cultivation in a good direction, the biggest threat is 40% from pests and diseases. The SWOT test results show total strengths of 1.13 and weaknesses of 11.35.